Characterization of Granular Materials with Internal Pores for Hydraulic Calculations Involving Fixed and Fluidized Beds - SOYER, ELİF; AKGİRAY, ÖMER (AMER CHEMICAL SOC, 2016)
This study focuses on the characterization of porous granular materials for applications in hydraulics of fixed and fluidized beds. Different density measurement procedures were tested using five different sieved fractions of each of zeolite, activated carbon, and anthracite coal media to compare these procedures and to ascertain the effect of the density measurement method used on the calculation of other particle and bed properties. The mentioned particle and bed properties are the following: (i) particle density, (ii) particle size (equivalent diameter), (iii) sphericity, (iv) fixed-bed porosity, and (v) expanded-bed porosity during fluidization. The density of each of the 15 fractions was determined using four different methods: (i) cone test (ASTM C128-12), (ii) Le Chatelier flask method, (iii) soaking and straining, and (iv) skeletal density. The first three of these measure wet density (i.e., pores filled with liquid), the difference between them being in how the particles are saturated with liquid before the density determinations. The results show that the standard cone test is the most suitable method for the type of applications considered in this work whereas the use of other simpler methods leads to varying degrees of error. An important finding of this work is that the fluidized-bed expansion data of the porous media studied here are in excellent agreement with the predictions of a correlation that Soyer and Akgiray (J. Water Supply: Res. Technol.--AQUA, 2009, 58, 336) developed by testing nonporous materials only.
Keywords: FILTER MEDIA; PACKED-BEDS; EXPANSION; BACKWASH; PREDICTION; WATER; FLOW